Peningkatan Kemampuan Keterampilan Basic Life Support (BLS) Melalui Pelatihan BLS Pada Perawat dan Bidan - Sugiyarto Sugiyarto; Dwi Sulistyowati ((JKG) Jurnal Keperawatan Global, 2020)
Background: In Hospital Cardiac Arrest (IHCA) is a major problem of patient safety and public health. the rescue action taken is Basic Life Support with CPR. BLS training needs to be provided to nurses and midwives in order to increase the ability of BLS skills. The purpose of this study was to analyze the effect of Basic Life Support (BLS) Training on the ability of BLS skills of Nurses and Midwives. Methods: This research is an experimental study with a Pre-Test-Post Test Group design approach through through testing the research hypothesis. The population of this study was nurses and midwives, amounting to 51 respondents with a total sampling technique so that the number of respondents was 51. Statistical tests in the paired group used the nonparametric Wilcoxon test. Results: Based on the Wilcoxon test results obtained a p value of 0,001 which means there is a difference between pre and post training, Conclusion: BLS training has an effect on improving the BLS skills of nurses and midwives. BLS skills training needs to be carried out on an ongoing basis so that nurses and midwives have good skills in conducting BLS.